Dynamin, encoded by shibire, is central to cardiac function. - Johnson, E.; Ringo, J.; Dowse, H. (Journal of Experimental Zoology, 2001)
Employing the Drosophila heart, a model system for genetic and molecular investigation of cardiac physiology, we demonstrate here an essential role for the protein dynamin, encoded by the Drosophila gene shibire(ts) (shi(ts)), in maintaining normal heart function. In flies bearing two temperature-sensitive alleles of shi, shi(ts1) and shi(ts2), heartbeat is both slower and less rhythmic than in wild-type animals. Serotonin and norepinephrine, normally cardioacceleratory in wild type, are without effect in flies bearing the shi mutation. Electrocardiogram (EKG) analysis reveals a bigeminal beat in mutant hearts, unlike the single electrical pulse in wild-type. The gene no action potential (temperature sensitive), with previously-described cardiac aberrations similar to those of shi, interacts with shi: shi/shi;nap/nap mutants have almost wild-type heart function. J. Exp. Zool. 289:81-89, 2001.